The Autonomy of Treaty Terms - Anna Michalska (Przegląd Prawniczy Uniwersytetu im. Adama Mickiewicza, 2019)
The paper is an English translation of Autonomiczność pojęć traktatowych by Anna Michalska published originally in Polish in “Toruński Rocznik Praw Człowieka i Pokoju” in 1993. The text is published as a part of a jubilee edition of the “Adam Mickiewicz University Law Review. 100th Anniversary of the Faculty of Law and Administration” devoted to the achievements of the late Professors of the Faculty of Law and Administration of the Adam Mickiewicz University, Poznań.